2018
DOI: 10.1107/s2056989018012161
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of FeN4at 180 GPa and its crystal structure from a submicron-sized grain

Abstract: The refined crystal structure model of iron tetra­nitride, FeN4, at 180 GPa is similar to that at 135 GPa but shows improved structural parameters in terms of bond lengths and angles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 23 publications
(22 reference statements)
2
33
0
Order By: Relevance
“…The crystal structures are then solved and refined within the JANA2006 software 32 . The procedure for single crystal X-ray diffraction data acquisition and analysis was previously demonstrated and successfully employed 13,14,33,34 . Powder X-ray diffraction was also performed to verify the chemical homogeneity of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…The crystal structures are then solved and refined within the JANA2006 software 32 . The procedure for single crystal X-ray diffraction data acquisition and analysis was previously demonstrated and successfully employed 13,14,33,34 . Powder X-ray diffraction was also performed to verify the chemical homogeneity of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of such dinitrides requires very high pressure above 40–50 GPa and a simple synthetic route, which was actively exploited in the recent years, is a direct reaction between a metal and nitrogen in a laser‐heated diamond anvil cell (LHDAC). This method was successfully used for the synthesis of transition metal dinitrides (PtN 2 , PdN 2 , IrN 2 , OsN 2 , TiN 2 , RhN 2 , RuN 2 , CoN 2 , CuN 2 , FeN 2 , CrN 2 ), polynitrides (FeN 4 ,, ReN 8 · N 2 ), and alkali metal pentazolates (LiN 5 , CsN 5 ). To scale up the production the synthesis should be carried out in a large‐volume apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…Recent high‐pressure studies have shown that various polynitrogen species may occur as a result of simple reaction between a metal and molecular nitrogen. Good examples of that are FeN 4 containing catena‐poly[tetraz‐1‐ene‐1,4‐diyl] anions [−N=N−N−N−] 2− ∞ , MgN 4 , and ReN 8 ⋅N 2 with polydiazenediyl (polyacetylene‐like) nitrogen chains . Thus, high‐pressure synthesis conditions enable the exploration of numerous possible metal–nitrogen framework topologies.…”
Section: Figurementioning
confidence: 99%